cultivo Respuesta del de col morada (Brassica oleracea) a la aplicación de abonos orgánicos en la zona de Babahoyo - Caicedo Chávez, Diego Armando (2015)
The research took place in the grounds of the experimental farm "San Pablo", which are located at Km 7.5 of the Babahoyo -Montalvo road. The objective was to analyze the agronomic performance of red cabbage crop to the application of three sources of organic fertilizers, to assess their effect on the performance of cabbages and crop development. Eight treatments formed by the worm humus fertilizer, and manure bovinaza investigated in doses of 5, 8; 8.10 and 5.8 kg / ha respectively and two witnesses with and without chemical fertilization, with four replicates and distributed in a randomized block design. The variables evaluated were: plant height, diameter and weight of cabbage, and crop yield. The evaluation of means was done with the Tukey test at 5% significance.